Strategic public investment: leverage support for competitiveness and development - Villalobos, Carlos Carranza (2020)
The reflection on the institutional capacities of the State and, specifically, of the Public Sector is an issue to be considered for countries that want to achieve a greater degree of development. Conceptual and practical efforts are a fundamental task; at this point, taking public investment as a reference constitutes a foundation of this process, since it is a bridge to achieve development objectives.Public investment, properly channeled, enables processes of well-being and competitiveness, through the creation of public value. This article synthesizes some questions about what could be called strategic public investment, especially that which helps to improvethe conditions of competitiveness and strengthen the conditions of sustainable development in the long term. There is a need for greater efforts to improve the destination of public investment so that it contributes to economic growth, strengtheningactivities or key areas for technological development, conditions for industrial parks or economic zones enable new ventures and strengthens national empowerment capacity. Collaterally, there are activities necessary for these purposes, such as the quality of public health, adequate infrastructure, modern sanitary systems and logistics for the mobilization of goods and resources, all part of the efforts that must be made from strategic public investment, whose destination must be clear and inadequate terms.